América Latina y la nueva legislación comercial de.Estados Unidos - Rodríguez Mendoza, Miguel (Estudios Internacionales, 1985)
This paper examines the fundamental aspects of the United States Trade and Tariffs Law and its possible consequences for Latin American countries. This new law is aimed at promoting the commercial interests of the United States on the basis of criteria of reciprocity and commercial retaliation and a more rigorous application of the procedures on safeguards and countervailing duties and anti-dumping. We argue, as a central thesis, that through this new law the restrictive nature of North American trade legislation is reinforced and the use of unilateral protection measures is encouraged, which can lead to a greater erosion of the multilateral trading system and affect the very negatively the commercial interests of developing countries, including Latin American countries.